Ovarian parameters and ovarian blood flow of women living in the area of environmental crisis. (May 2016) - Balmagambetova, Aru; Abdelazim, Ibrahim A.; Bekmukhambetov, Erbol; Zhurabekova, Gulmira; Yehia, Amr H.; AbuFaza, Mohannad
Abstract: Background and objectives: Exposure to environmental hazards will destroy a number of ovarian primordial follicles, reduce ovarian reserve and subsequent reproductive ability. This study designed to evaluate ovarian parameters and ovarian blood flow of women living in the area of environmental crisis Shalkar city (Kazakhstan) compared to women living in Aktobe city (Kazakhstan). Patients and methods: 220 women in their reproductive age studied and classified into two groups; study (Shalkar) group and control (Aktobe) group. Blood sample taken from studied women during follicular phase (day 3) for hormonal level evaluation including; follicle stimulating hormone (FSH) and anti-Mullerian hormone (AMH). Studied women evaluated using trans-vaginal ultrasound (TVS) to detect antral follicle count (AFC) during follicular scan and ovarian volume (OV), ovarian blood flow (OBF) using pulsatility index (PI) during follicular scan and luteal scan. Results: Both ovaries AFC was significantly less in study (Shalkar) group compared to and control (Aktobe) group ( p = 0.0001). Mean ovarian volume was significantly less in Shalkar group in both follicular phase and luteal phase (5.86 ± 0.23 and 6.19 ± 0.22 Cm 3 ; respectively) compared to Aktobe group (6.85 ± 0.19 and 6.92 ± 0.18 Cm 3 ; respectively). In addition, mean ovarian pulsatility index was significantly high with subsequent decrease in ovarian blood flow in Shalkar group in both follicular phase and luteal phase (3.36 ± 0.20 and 3.45 ± 0.19 Cm/s; respectively) compared to Aktobe group (2.96 ± 0.16 and 2.92 ± 0.15 Cm/s; respectively). Conclusion: This study suggests definite environmental effect on ovarian parameters as indicated by decreased AFC, decreased both follicular and luteal OV and OBF in women living in environmental crisis Shalkar group compared to Aktobe group.